Les développements possibles de la protection internationale des minorités - Capotorti, Francesco (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Internationally, the basis for the legal protection of minorities is found in the International Covenant for Civil and Political Rights. In order to appraise the scope of this regime, the author first questions the degree to which protection provided under standards laid down in the Covenant may be sufficient. To this end, he distinguishes elements of non-discrimination and special measures for protecting minorities for which he underscores the genuine difficulties in applying them. The author then questions the feasibility of devising other means likely to improve the fate of minorities that would not upset the delicate balance of Covenants. In such a perspective, he recommends the drafting of a Declaration by the United Nations General Assembly concerning minorities. He also draws attention to the hypothesis of developing international protection for minorities by increasingly resorting to local and territorial legal instruments by proposing greater usage of international means for implementing human rights.